Sistem Informasi Kelurahan Koto Panjang Kota Solok Berbasis Web - Ningsih, Silvia (ITB Ahmad Dahlan Jakarta, 2022)
After conducting research at the Koto Panjang Village Head Office, problems were found regarding the preparation of certificates, which still used Microsoft Word. This results in the report requested by the leadership not being accurate, fast and timely. In writing this thesis, the research method used was field research, namely interviews by asking questions through question and answer, library research and research in the laboratory using the PHP programming language and MySql database. By utilizing a computerized system and the PHP programming language, it is hoped that it can help the process of creating certificates using storage media in the MySQL database, it is hoped that it can replace methods that are less efficient and effective and is expected to make reporting easier.